Cognitive Function in Patients Undergoing Arthroplasty: The Implications for Informed Consent. (20th June 2011) - Demosthenous, N.; St Mart, J. P.; Jenkins, P.; Chappel, A.; Cheng, Kenneth
Abstract : Obtaining informed consent for an operation is a fundamental daily interaction between orthopaedic surgeon and patient. It is based on a patient's capacity to understand and retain information about the proposed procedure, the potential consequences of having it, and the alternative options available. We used validated tests of memory on 59 patients undergoing lower limb arthroplasty to assess how well they learned and recalled information about their planned procedure. All patients showed an ability to learn new material; however, younger age and higher educational achievement correlated with better performance. These results have serious implications for orthopaedic surgeons discussing planned procedures. They identify groups of patients who may require enhanced methods of communicating the objectives, risks, and alternatives to surgery. Further research is necessary to assess interventions to improve communication prior to surgery.